HUBUNGAN TINGKAT PENGETAHUAN IBU TERHADAP PERKEMBANGAN MOTORIK ANAK USIA BALITA - Eko Sri Wulaningtyas; Entin Srihadi Yanti; Mulazimah Mulazimah (Jurnal EDUNursing, 2022)
An important period in a child's growth and development is the toddler period. The stage of child development is a critical period, where appropriate stimulation or stimulus is needed so that the potential that exists in children develops optimally, so that during this development period, attention is needed, especially from the mother. Therefore, good knowledge is needed in providing stimulation for children's motor development. This study aims to determine the level of mother's knowledge of the motor development of children under five at Dharma Wanita Kindergarten, Ringinsari Village, Kediri. The methodology used in this study is correlational. The number of samples is 30 taken by purposive sampling technique. Data was collected using a questionnaire and data processing was carried out by analysis of the Rankspearman test. The results of this study were from a total of 30 respondents, it was found that mothers with less knowledge had children with deviant motor development (70%), mothers with sufficient knowledge had children with doubtful motor development (13.33%) and deviant (3.33%) ), mothers with good knowledge have children with good motor development (10%) and doubts (3.33%). From the results of the Rankspearman test analysis, the results of the p value = 0.000 (< 0.05), so in this study it can be stated that H1 is accepted, namely there is a relationship between mother's knowledge of motor development of children under five in Dharma Wanita Kindergarten, Ringinsari Village, Kediri Keywords: Knowledge level, motor development, toddler